Multi agent-based electronic commerce transactions - Wang, Guandong (2008)
This thesis is mainly to investigate the complex transactions, especially in agent-based e-commerce systems. To start with, we provide a formal definition for general e-commerce transactions. Consistent with the definition, we propose a graph model (the Electronic Transaction Graph or ETG) to represent complex e-commerce transactions by labeled directed graphs.